If some is good, more is better: An enoxaparin dosing strategy to improve pharmacologic venous thromboembolism prophylaxis. Issue 6 (December 2016) - Berndtson, Allison E.; Costantini, Todd W.; Lane, James; Box, Kevin; Coimbra, Raul
Abstract : BACKGROUND: Empiric enoxaparin dosing is inadequate for most trauma patients, leading to below target initial anti-Xa levels and requiring dose adjustment for optimal venous thromboembolism prophylaxis. We hypothesize that patient factors affecting initial anti-Xa levels can be identified based on drug pharmacokinetics, allowing creation of a new dosing protocol that will provide a higher percentage of in-target (0.2–0.4 IU/mL) patients at initial anti-Xa level assessment. METHODS: Records of 318 trauma patients were evaluated, and NONMEM and PSN software were used to analyze 11 variables for their effects on anti-Xa levels. Computer modeling was used to select a new dosing protocol, which was implemented on the trauma service as a quality improvement project. The first 145 patients appropriately enrolled were assessed for response and complications. RESULTS: Only 29.5% of the pre-intervention group had initial anti-Xa levels in the appropriate prophylactic range (Fig. 1 ). Levels were most strongly influenced by patient weight, outweighing contributions from all other variables. A new regimen for initial dosing was therefore designed with three weight-defined categories for ease of administration. The post-intervention group showed an increase in in-target initial anti-Xa levels to 74.5% ( p < 0.001), with a corresponding decrease in subprophylactic patients from 68.0% to 20.7%. There was an increase in supraprophylactic levels to 4.8%, but no supraprophylactic patients had hemorrhagic complications. CONCLUSIONS: Implementation of a new, categorized, weight-based enoxaparin dosing protocol was safe and significantly improved the percentage of trauma patients with in-target anti-Xa levels on initial assessment. Further studies are needed to determine whether such dosing decreases venous thromboembolism rates. LEVEL OF EVIDENCE: Therapeutic/care management study, level II.